Analisis Upaya Pemerintah Dalam Menangani Mudik Melalui Peraturan Menteri Perhubungan Nomor 25 Tahun 2020 Pada Masa Covid-19 - Nadine, Ainaya; Imtiyaz, Zulfa Zahara (Media Iuris, 2020)
Covid-19 is a contagious disease that causes emergencies in the world including Indonesia. This situation causes all activities to be hampered, especially in terms of mobility that is needed to carry out activities. Transportation is an important tool in this regard. The government is demanding that as soon as possible take steps to prevent and control the spread of Covid-19, so a rule or regulation is needed. The spread of Covid-19 in Indonesia, which began in March 2020, continued until the Eid 1441 H took place. It has become a culture and tradition in Indonesia when Eid is to stay in touch with relatives and return to their hometown or usually called mudik. This of course requires a mode of transportation. To prevent the acceleration of the spread of the virus, the government issued a regulation on the prohibition of mudik through Permenhub No. 25/2020. The issuance of this regulation is a government preventive measure in handling Covid-19. However, this causes losses to prospective passengers who have already bought tickets for going home and those who hope to meet with their families. Regarding this, regulation must not only contain regulatory matters such as prohibitions and sanctions for those who violate them but also provide solutions to unwanted things such as compensation as a form of liability. However, whether law enforcement and the application of this regulation are effective according to government directives or not.